Fragmenternes liv: Paul la Cours vitalistiske poetik - Ehlers Dam, Anders (Danske Studier, 2024)
The traditional readings of Paul la Cour’s poetics, Fragmenter af en Dagbog [Fragments of a Diary](1948) focus mainly on the poetological and philosophical reflexions in the work. Its form and rhetorics have been shunned or outright dismissed as a disturbance for its content. In this article, I focus on form in la Cour’s work, whose source of inspiration are writings like Heraclitus’ fragments and the poetics of the modern French poets. La Cour himself considered the form of his poetics modernist. I argue that la Cour’s work has actually no specific genre, but contains traits of various genres: the fragmentary, the aphoristic, and the diaristic. While the fragmentary indicates infinity and interruption, the aphoristic is pointed, paradoxical and momentary. The diary acts as a frame for both the fragmentary and the aphoristic. I contend that the pathos-infused style of la Cour’s work can be explained as an effect of the aphoristic writing style. Finally, I use Henri Bergson’s philosophy to suggest a vitalistic reading strategy, which requires not only an intellectual understanding of la Cour’s thought, but also a concomitant experiencing of the form of the book in the concrete reading process.